Augustea (Polycarpaeae, Caryophyllaceae), a new genus from South America - Iamonico, Duilio (Phytotaxa, 2015)
Recent published molecular analyses have shown that the genus Polycarpon is polyphyletic and includes only the members belonging to the Polycarpon tetraphyllum aggregate. Morphologically, dehiscence of the capsule by valves that elastically roll inwards and eject the seeds provides a clear synapomorphy for Polycarpon in this restricted sense. Among the excluded taxa, the South American P. anomalum, P. suffruticosum and P. coquimbense are not described taxonomically, although molecular and morphological evidence exists. We here propose to recognise these species as a new South American endemic genus (Augustea gen. nov.) with three recognized species. The names Polycarpon suffruticosum (var. suffruticosum, and var. virens), P. australe, and P. anomalum are lectotypified. A diagnostic key is provided, as well as descriptions, ecological information and distribution for each species.